ALLERGIC CONJUNCTIVITIS IN CHILDHOOD - Barros de Sá, Janilson; Carvalho de Sá, Vinicius; Guilherme de Sá Santos, João (Health and Society, 2024)
Allergic conjunctivitis is an eye condition prevalent among children, characterized by inflammation of the conjunctiva resulting from an allergic reaction to substances such as pollen, dust, dust mites and animal dander. This disease is a manifestation of the immune system and causes symptoms such as intense itching, tearing, hyperemia and a sensation of a foreign body in the eyes. The management of allergic conjunctivitis ranges from simple measures, such as frequent eye washing and avoidance of allergens, to the use of medications such as antihistamines, mast cell stabilizers and topical corticosteroids. In childhood, the management of allergic conjunctivitis faces difficulties such as variability in response to treatment and the impossibility of completely avoiding exposure to allergens. The general objective of this study is to evaluate management strategies for allergic conjunctivitis in childhood, with an emphasis on the effectiveness of available treatments and the identification of factors that influence the response to treatment. Specific objectives include analyzing the effectiveness of different treatments, investigating the influence of environmental and individual factors on disease severity and recurrence, and discussing the management of allergic conjunctivitis. This study is relevant as appropriate management of allergic conjunctivitis can prevent complications and improve children’s well-being. Identifying factors that influence response to treatment can contribute to the development of more personalized and effective therapeutic approaches. Recent literature highlights the need to improve education of parents and caregivers about allergic conjunctivitis to ensure appropriate management of the disease. Studies show that understanding the immunological mechanisms underlying the disease is crucial for developing new therapies. Therefore, this research not only adds to scientific knowledge about childhood allergic conjunctivitis, but also provides valuable insights for clinical practice and health policy formulation.